Reduced gene expression of bikunin as a prognostic marker for renal cell carcinoma - Bayraktar, E.; Igci, M.; Erturhan, S.; Igci, Y.Z.; Karakok, M.; Gogebakan, B.; Ulasli, M.; Cakmak, E.A.; Arslan, A. (Experimental Oncology, 2014)
Aim: Experimental and clinical studies showed that bikunin, a Kunitz-type protease inhibitor, found in urine and amniotic fluid has a role in spread of tumor cells by providing a significant reduction in the levels of urokinase-type plasminogen activator (uPA) and its specific receptor urokinase-type plasminogen activator receptor (uPAR). The aim of this study was to investigate expression of bikunin at the mRNA level and screen for mutations in exon sequence in renal cell carcinoma (RCC) tissues. Materials and Methods: Total RNA and DNA were extracted from paired normal and tumor tissues of total 50 RCC (11 papillary, 8 chromophobe, 26 clear cell, and 5 other types) patients (23 females, mean age: 53.55 ± 14.17; 27 males mean age: 62.1 ± 7.92). Bikunin mRNA levels were detected using semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR). Mutational screening was performed by using single strand conformation polymorphism (SSCP) method and nucleotide sequence analysis. Results: There was a statistically significant decrease in the 25 (50%) of tumor tissues comparing to normal tissues in terms of mRNA levels of bikunin (Wilcoxon signed rank test, p = 0.0337). According to the classification based on subtypes of RCC; clear cell RCC samples displayed a reduced gene expression (p = 0.0148). Additionally, the patients with the age above 50 had low bikunin expression. The SNP rs80057939 spanning 4th exon of bikunin was detected in 13 tumor tissues. However, it was not statistically significant (p > 0.05). Conclusion: Decreased bikunin mRNA level in renal cells might be associated with poor prognosis of renal carcinoma. Therefore, gene constructs or exogenous administration of bikunin might be a potential adjuvant therapy for RCC treatment. Key Words: Bikunin, nucleotide sequence analysis, prognostic marker, renal cell carcinoma, semi-quantitative RT-PCR.